2014
DOI: 10.1111/his.12545
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating encounters of atypical ductal hyperplasia arising in gynaecomastia

Abstract: ADH in gynaecomastia can be distinguished from UDH by morphological and immunohistochemical features. We also identified a subset of young patients (< 25 years) with extensive bilateral ADH. More studies are needed to characterize this patient subset more clearly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The recent study by Wells et al of atypical ductal hyperplasia arising in gynecomastia demonstrated the usefulness of CK5/6 and ER staining in discriminating usual ductal hyperplasia from ADH and DCIS in gynecomastia. 5 Moreover, with diminishing reactivity for CK5/6 positive luminal epithelial cells in ADH compared with UDH, the authors concluded that ADH in this context may represent a transitional state in the evolution of DCIS in some cases but that if the pathway exists, it is not a well-utilized one. In contrast, Kornegoor et al suggest that gynecomastia does not seem to be an obligate precursor to breast cancer as it is a proliferation of 2 different cell types.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The recent study by Wells et al of atypical ductal hyperplasia arising in gynecomastia demonstrated the usefulness of CK5/6 and ER staining in discriminating usual ductal hyperplasia from ADH and DCIS in gynecomastia. 5 Moreover, with diminishing reactivity for CK5/6 positive luminal epithelial cells in ADH compared with UDH, the authors concluded that ADH in this context may represent a transitional state in the evolution of DCIS in some cases but that if the pathway exists, it is not a well-utilized one. In contrast, Kornegoor et al suggest that gynecomastia does not seem to be an obligate precursor to breast cancer as it is a proliferation of 2 different cell types.…”
Section: Discussionmentioning
confidence: 98%
“…They included 25 cases of ADH with gynecomastia, 9 cases of DCIS (2 of which had concurrent ADH), and 36 cases of gynecomastia with usual ductal hyperplasia. 5 Moreover, while usual ductal hyperplasia and ADH as well as invasive and noninvasive breast carcinoma in males can be concurrent with gynecomastia, to date, no cases have shown ADH and DCIS with features of gynecomastia and associated invasive carcinoma. 1-7 Columnar cell-like change has been reported in a series of male breast resections, some of which showed gynecomastoid hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a patient undergoes surgery for gynecomastia, pathologic analysis of the excised tissue is generally recommended to rule out occult breast cancer or other incidental findings [1][2][3]. The incidence of atypical ductal hyperplasia (ADH) in gynecomastia specimens ranges from 0.4-5.4% [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first report of atypical ductal hyperplasia with microcalcifications in a male patient [ 4 ]. Consequently, insufficient evidence exists to support the hypothesis that this condition is a risk factor for male breast cancer, as it is for females.…”
mentioning
confidence: 99%